PERSEPSI TENTANG MITOS DAN PANTANGAN MAKANAN SELAMA KEHAMILAN DALAM PERSPEKTIF BUDAYA JAWA - Fifi Nur Fathonah; Yektiningtyastuti Yektiningtyastuti (Jurnal Kesehatan dan Pembangunan, 2026)
Pregnancy is a complex physiological process that requires special attention to ensure it proceeds normally without complications. One of the key concerns during pregnancy is maintaining adequate nutrition to support fetal growth. Many pregnant women still experience Chronic Energy Deficiency (CED) due to dietary patterns influenced by myths and food taboos in Javanese culture. This study examines pregnant women's perceptions of myths and food taboos during pregnancy from a Javanese cultural perspective. This study is a quantitative descriptive study with a sample of 34 pregnant women. The research instrument used a questionnaire to measure pregnant women's perceptions of myths and food taboos, which were valid (r = 0.507 - 0.822) and reliable (?-Cronbach = 0.926). Univariate analysis of the study results showed that 55.9% of pregnant women had positive perceptions, and 44.1% had negative perceptions. The results of this study indicate that 44.1% of pregnant women in Lesmana Village, Banyumas Regency, have negative perceptions of myths and food taboos. This can increase the risk of CED in pregnant women in Lesmana Village. Health education or counseling is needed to dispel myths and taboos.